Dinucleotide preferences underlie apparent codon preference reversals in the Drosophila melanogaster lineage - Haruka Yamashita; Tomotaka Matsumoto; Kent Kawashima; Hassan Sibroe Abdulla Daanaa; Ziheng Yang; Hiroshi Akashi (Proceedings of the National Academy of Sciences, 2025)
We employ fine-scale population genetic analyses to reveal dynamics among interacting forces that act at synonymous sites and introns among closely related Drosophila species. Synonymous codon usage bias has proven to be well suited for population genetic inference. Under major codon preference (MCP), translationally superior “major” codons confer fitness benefits relative to their less efficiently and/or accurately decoded synonymous counterparts. Our codon family and lineage-specific analyses expand on previous findings in the Drosophila simulans lineage; patterns in naturally occurring polymorphism demonstrate fixation biases toward GC-ending codons that are consistent in direction, but heterogeneous in magnitude, among synonymous families. These forces are generally stronger than fixation biases in intron sequences. In contrast, population genetic analyses reveal unexpected evidence of codon preference reversals in the Drosophila melanogaster lineage. Codon family-specific polymorphism patterns support reduced efficacy of natural selection in most synonymous families but indicate reversals of favored states in the four codon families encoded by NAY. Accelerated synonymous fixations in favor of NAT and greater differences for both allele frequencies and fixation rates among X-linked, relative to autosomal, loci bolster support for fitness effect reversals. The specificity of preference reversals to codons whose cognate tRNAs undergo wobble position queuosine modification is intriguing. However, our analyses reveal prevalent dinucleotide preferences for ApT over ApC that act in opposition to GC-favoring forces in both coding and intron regions. We present evidence that changes in the relative efficacy of translational selection and dinucleotide preference underlie apparent codon preference reversals.